The Role of Spirituality in the Lives of Women Coping with Early Motherhood and Postpartum Depression - Martins, Sandra (Université Saint-Paul / Saint Paul University, 2018)
The present qualitative study explored women’s lived experiences of early motherhood, spirituality, and postpartum depression with the aim of better understanding the role spirituality plays in the lives of women coping with early motherhood and postpartum depression. Semi-structured interviews were conducted with six women with a child under the age of 18 months, two of whom self-identified with postpartum depression. Interview transcripts were analyzed using Interpretative Phenomenological Analysis and led to the emergence of three super-ordinate themes: Realities of Motherhood, Realities of Postpartum Depression, and Motherhood Awakens Spirituality. Motherhood emerged as a catalyst for spiritual development and renewal while spirituality played an important role in coping and contributed to the formation of self-conceptualizations of motherhood. Postpartum depression was manifest around issues of the self and closely associated with prolonged spiritual struggle. A model is proposed delineating the interconnectivity and movement of early motherhood and spirituality toward personal and spiritual transformation.
Keywords: motherhood; spirituality; postpartum depression; transition; coping; identity